Incidence of Sudden Cardiac Death and Life-Threatening Arrhythmias in Clinically Manifest Cardiac Sarcoidosis With and Without Current Indications for an Implantable Cardioverter Defibrillator - Nordenswan Hanna-Kaisa; Pöyhönen Pauli; Lehtonen Jukka; Ekström Kaj; Uusitalo Valtteri; Niemelä Meri; Vihinen Tapani; Kaikkonen Kari; Haataja Petri; Kerola Tuomas; Rissanen Tuomas T; Alatalo Aleksi; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Background:
Cardiac sarcoidosis (CS) predisposes to sudden cardiac death (SCD). Guidelines for implantable cardioverter defibrillators (ICDs) in CS have been issued by the Heart Rhythm Society in 2014 and the American College of Cardiology/American Heart Association/Heart Rhythm Society consortium in 2017. How well they discriminate high from low risk remains unknown.
Methods:
We analyzed the data of 398 patients with CS detected in Finland from 1988 through 2017. All had clinical cardiac manifestations. Histological diagnosis was myocardial in 193 patients (definite CS) and extracardiac in 205 (probable CS). Patients with and without Class I or IIa ICD indications at presentation were identified, and subsequent occurrences of SCD (fatal or aborted) and sustained ventricular tachycardia were recorded, as were ICD indications emerging first on follow-up.
Results:
Over a median of 4.8 years, 41 patients (10.3%) had fatal (n=8) or aborted (n=33) SCD, and 98 (24.6%) experienced SCD or sustained ventricular tachycardia as the first event. By the Heart Rhythm Society guideline, Class I or IIa ICD indications were present in 339 patients (85%) and absent in 59 (15%), of whom 264 (78%) and 30 (51%), respectively, received an ICD. Cumulative 5-year incidence of SCD was 10.7% (95% CI, 7.4%-15.4%) in patients with ICD indications versus 4.8% (95% CI, 1.2%-19.1%) in those without (chi(2)=1.834, P=0.176). The corresponding rates of SCD were 13.8% (95% CI, 9.1%-21.0%) versus 6.3% (95% CI, 0.7%-54.0%; chi(2)=0.814, P=0.367) in definite CS and 7.6% (95% CI, 3.8%-15.1%) versus 3.3% (95% CI, 0.5%-22.9%; chi(2)=0.680, P=0.410) in probable CS. In multivariable regression analysis, SCD was predicted by definite histological diagnosis (P=0.033) but not by Class I or IIa ICD indications (P=0.210). In patients without ICD indications at presentation, 5-year incidence of SCD, sustained ventricular tachycardia, and emerging Class I or IIa indications was 53% (95% CI, 40%-71%). By the American College of Cardiology/American Heart Association/Heart Rhythm Society guideline, all patients with complete data (n=245) had Class I or IIa indications for ICD implantation.
Conclusions:
Current ICD guidelines fail to distinguish a truly low-risk group of patients with clinically manifest CS, the 5-year risk of SCD approaching 5% despite absent ICD indications. Further research is needed on prognostic factors, including the role of diagnostic histology. Meanwhile, all patients with CS presenting with clinical cardiac manifestations should be considered for an ICD implantation.